Intangible Capital and Firm-Level Productivity – Evidence from Germany - Felix Roth; Ali Sen; Christian Rammer (University of Hamburg, Chair of International Economics, 2021)
This paper analyses the impact of intangible capital on firm-level productivity for Germany using panel data from the Community Innovation Survey for the time period 2006 to 2018. Our paper presents three novel results. First, we find a highly significant positive relationship between intangible capital and firm-level productivity with elasticities overall in line with previous findings reported for other large EU economies. Second, our results show that both manufacturing and services are highly intangible-capital intensive, and that intangibles have a greater impact on firm-level productivity in services - particular in the business services sector. Third, our results show that intangible capital investments in German firms are equal to investments in tangible capital since the early 2000s. Overall, the evidence presented in our paper indicates that Germany - in line with other advanced economies - has undergone a structural transition into a knowledge economy in which intangibles act as an important driver of firm-level productivity.
Keywords: D24; O30; L22; C33; 330; Intangible capital; firm-level productivity; panel data; Germany